Fuel for economic growth? - Johan Gars; Conny Olovsson (Sveriges Riksbank, 2015)
We set up an endogenous growth model in which the efficiency of both capital and fossil energy can be improved, whereas the efficiency of one alternative energy source is limited. With capital and energy as complements, there exist two steady states: one stagnant where energy is fully derived from the alternative energy source, and one with balanced growth where energy is fully sourced from fossil fuel. Heterogeneity in initial TFP levels can generate the Great Divergence. The demand for fossil fuel in technologically advanced countries drives up its price and makes fossil fuel too costly in less advanced countries that choose the alternative and stagnant energy input.
Keywords: O11; O14; O33; O41; O50; 330; Growth; Malthusian stagnation; Industrial Revolution; Great Divergence; Technological progress